Counter pressure maneuvers for syncope prevention: A semi-systematic review and meta-analysis - Williams, Erin Lori; Khan, Farhaan Muhammad; Claydon, Victoria Elizabeth (Frontiers in Cardiovascular Medicine, 2022)
Physical counter pressure maneuvers (CPM) are movements that are recommended to delay or prevent syncope (fainting) by recruiting the skeletal muscle pump to augment cardiovascular control. However, these recommendations are largely based on theoretical benefit, with limited data evaluating the efficacy of CPM to prevent syncope in the real-world setting. We conducted a semi-systematic literature review and meta-analysis to assess CPM efficacy, identify literature gaps, and highlight future research needs. Articles were identified through a literature search (PubMed, April 2022) of peer-reviewed publications evaluating the use of counter pressure or other lower body maneuvers to prevent syncope. Two team members independently screened records for inclusion and extracted data. From 476 unique records identified by the search, 45 met inclusion criteria. Articles considered various syncopal conditions (vasovagal = 12, orthostatic hypotension = 8, postural orthostatic tachycardia syndrome = 1, familial dysautonomia = 2, spinal cord injury = 1, blood donation = 10, healthy controls = 11). Maneuvers assessed included hand gripping, leg fidgeting, stepping, tiptoeing, marching, calf raises, postural sway, tensing (upper, lower, whole body), leg crossing, squatting, “crash” position, and bending foreword. CPM were assessed in laboratory-based studies (N = 28), the community setting (N = 4), both laboratory and community settings (N = 3), and during blood donation (N = 10). CPM improved standing systolic blood pressure (+ 14.8 ± 0.6 mmHg, p < 0.001) and heart rate (+ 1.4 ± 0.5 bpm, p = 0.006), however, responses of total peripheral resistance, stroke volume, or cerebral blood flow were not widely documented. Most patients experienced symptom improvement following CPM use (laboratory: 60 ± 4%, community: 72 ± 9%). The most prominent barrier to employing CPM in daily living was the inability to recognize an impending faint. Patterns of postural sway may also recruit the skeletal muscle pump to enhance cardiovascular control, and its potential as a discrete, proactive CPM needs further evaluation. Physical CPM were successful in improving syncopal symptoms and producing cardiovascular responses that may bolster against syncope; however, practical limitations may restrict applicability for use in daily living.